Validating the efficacy and value proposition of mental fitness vocal biomarkers in a psychiatric population: prospective cohort study - Larsen, Erik; Murton, Olivia; Song, Xinyu; Joachim, Dale; Watts, Devon; Kapczinski, Flavio; Venesky, Lindsey; Hurowitz, Gerald (Frontiers in Psychiatry, 2024)
Background The utility of vocal biomarkers for mental health assessment has gained increasing attention. This study aims to further this line of research by introducing a novel vocal scoring system designed to provide mental fitness tracking insights to users in real-world settings. Methods A prospective cohort study with 104 outpatient psychiatric participants was conducted to validate the “Mental Fitness Vocal Biomarker” (MFVB) score. The MFVB score was derived from eight vocal features, selected based on literature review. Participants’ mental health symptom severity was assessed using the M3 Checklist, which serves as a transdiagnostic tool for measuring depression, anxiety, post-traumatic stress disorder, and bipolar symptoms. Results The MFVB demonstrated an ability to stratify individuals by their risk of elevated mental health symptom severity. Continuous observation enhanced the MFVB’s efficacy, with risk ratios improving from 1.53 (1.09-2.14, p=0.0138) for single 30-second voice samples to 2.00 (1.21-3.30, p=0.0068) for data aggregated over two weeks. A higher risk ratio of 8.50 (2.31-31.25, p=0.0013) was observed in participants who used the MFVB 5-6 times per week, underscoring the utility of frequent and continuous observation. Participant feedback confirmed the user-friendliness of the application and its perceived benefits. Conclusions The MFVB is a promising tool for objective mental health tracking in real-world conditions, with potential to be a cost-effective, scalable, and privacy-preserving adjunct to traditional psychiatric assessments. User feedback suggests that vocal biomarkers can offer personalized insights and support clinical therapy and other beneficial activities that are associated with improved mental health risks and outcomes.